Status of varietal improvement in sesame (Sesamum indicum L.) in ANGRAU, Andhra Pradesh: Status of varietal improvement in sesame (Sesamum indicum L.) in ANGRAU, Andhra Pradesh - N SABITHA; S V S GANGADHARA RAO (Journal of Oilseeds Research, 2020)
Sesame is grown in area of 64000 hectares in Andhra Pradesh producing 16000 tons with a productivity of 257 kg/ha. It is cultivated both in kharif and rabi seasons mostly in West Godavari, Visakhapatnam, Srikakulam, Vizianagaram, Kadapa, Krishna, Guntur and Kurnool districts. The state average yields are low when compared to the national average yields. The major constraints in improving productivity include non-availability of location and season specific improved varieties with high yield and oil content, severe incidence of phyllody under late sown conditions, seed shattering and non-availability of early maturing varieties.